Ent-Pimaradiene and cyathane diterpenes from Aleuritopteris albofusca. (December 2020) - Jiang, Can; Chen, Junping; Dai, Xiling; Wang, Qi; Cao, Jianguo; Huang, Guozheng
Graphical abstract: Highlights: Chemical constituents of the fern A. albofusca was investigated for the first time. Two previously undescribed diterpenoids were isolated. High yield of onychiol B implied cyathanes might truly be produced by ferns. Abstract: An ent -pimaradiene diterpene, ent -8(14), 15-pimaradiene-2 β, 19-diol (1 ), and a cyathane diterpene, 14-oxy-7 α, 20-dihydroxycyath-12, 18-diene (2 ), together with seven known natural products (3 -9 ) were isolated from Aleuritopteris albofusca . Their structures were established by means of 1D and 2D NMR, IR, MS, and single-crystal X-ray methods and comparison with data of known analogs. The large amount of onychiol B in A. albofusca suggested that cyathane diterpenoids may be produced not only by fungi but also by ferns and higher plants.